PENGARUH MEDROKSI PROGESTERON ASETAT TERHADAP ULTRASTRUKTUR SEL LEYDIG TIKUS PUTIH (Rattus norvegicus) - Sarmanu (The East Java Biological Society, 1999)
The objective of the research was to study the effect of medroxy progesterone acetate on the ultrastructure of Leydig cells of Rattus norvegicus. Randomized complete design was applied to study. Treatment consisted of 4 doses medroxy progesterone acetate were 0, 4, 8 and 12 mg per rat respectively and 8 replications. Injection were applied perform 4 times per rat within 4 weeks interval. The testicle were examined ultrastructure change on the nucleus, endoplasmic reticulum, mitochondria and golgy apparatus of the Leydig cells. Results indicated that injections of medroxy progesterone acetate of 8 and 12 mg per rat causes significant untrastructure change of nucleus, endoplasmic reticulum, Golgi apparatus and mitochondria of Leydig cells in comparison with doses 0 and 4 mg per rat. In additions, there were no significant different in ultrastructure of Leydig cells between doses 8 and 12 mg per rat as well as there were no significant different between doses of 4 and 0 mg per rat.